Physicochemical characterization of seed and seed oil of Jatropha curcas L. Collected from Bardoli (South Gujarat) - Bhavesh S. Nayak; K.N. Patel (Universiti Kebangsaan Malaysia, 2010)
The seed of Jatropha curcas was collected from the outskirts region of the Bardoli (Gujarat) and it was utilized for determination of seed characterization. The Jatropha curcas oil was extracted using light petroleum ether (60-80°C) by Soxhlet apparatus. The physicochemical properties of Jatropha curcas oil were evaluated. The result showed that the seeds consist of 46.31% (dry w/w) oil, moisture and volatilities (5.8% v/w) and protein content (22.50%). The physicochemical properties shows acid value (36.46), iodine value (106.00 mg/g) and saponification value (194.70 mg/g). The unsaponifiable matter was 1.02%. Negative Halphen test indicated the absence of cyclopropanoid acids in seed oil. GC analysis of J. curcas oil showed presence of palmitic acid (16.69%), stearic acid (7.67%), oleic acid (40. 39%) and linoleic acid (33.09%).